Russian Religious Reformation Process of Early 20th Century through Prism of Ideological Quests of Fr. Mikhail (Semenov) - D. A. Golovushkin (Научный диалог, 2024)
The article examines the development of views on the reform of Russian Orthodoxy in the early 20th century by one of the prominent and unconventional religious thinkers of that time, Father Mikhail (Pavel Vasilievich Semenov, 1873-1916). It traces his journey from official Orthodoxy to the movement for religious renewal, and then to the Belokrinitskaya (or Austrian) Old Believer hierarchy, after which he becomes the main ideologist of “Golgotha Christianity” — a unique religious-reformist movement advocating for the revival of social and moral ideals of the early Christian community. As contemporaries noted, these “oscillations” of Father Mikhail (Semenov) became a natural expression of his intense quest for the kerygma of Christianity, capable of overturning the social ontology of the Orthodox Church — finding an Orthodox formula for individualizing faith and making the world the goal of salvation. The author concludes that the life path and ideological quests of Father Mikhail (Semenov) reflect an important regularity of the Russian reformation process. This regularity lies in the fact that the search for “foundations” of faith, theological foundations of doctrine, or religious foundations of culture and society is simultaneously associated with the actualization of a fundamentalist impulse in religion and to some extent with the modernization of the religious complex (this is a kind of religious swing: “fundamentalism — modernism,” “Old Believers — religious renewal,” etc.).